CONTENT, QUANTITY AND DISTRIBUTION OF LOADS IN MONTHLY MESOCYCLE AND WEEKLY MICROCYCLES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the structure of the amount of loads during the training and competition periods within the monthly mesocycle (by weeks) and weekly microcycles (between trainings).